Responses of Pre-Service Chemistry Teachers at UIN Walisongo Semarang towards e-Learning Management System during Covid-19 Pandemic - Yulia Widayanti; Siti Rahmawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: This study aims to analyze the response of UIN Walisosngo Semarang students to the e-learning system during the COVID-19 pandemic. Quantitative descriptive is the method used in this study with the research instrument in the form of a response questionnaire given to students using the google form. The subjects of this research are 21 pre-service chemistry teacher. The results showed that the e-learning learning media applied during online learning was very beneficial for students. This is evidenced by the student's response to the questions given at the time of filling out the questionnaire by showing quite positive results with an average of 63.81% who answered agree. Based on the data obtained from the research, it shows that e-learning can be applied in online learning at UIN Walisongo Semarang. However, the use of e-learning must always be improved to achieve better learning goals. Keywords: e-learning management system, pre-service chemistry teachers, covid-19 pandemic. Abstrak: Penelitian ini bertujuan untuk menganalisis respons mahasiswa UIN Walisosngo Semarang terhadap sistem e-learning selama pandemi COVID-19. Deskriptif kuantitatif merupakan metode yang digunakan dalam penelitian ini dengan instrument penelitiannya adalah berupa angket respons yang diberikan kepada mahasiswa menggunakan google form. Subjek dari penelitian ini mahasiswa Pendidikan Kimia yang berjumlah 21 (dua puluh satu) orang. Hasil dari penelitian menunjukkan bahwa media pembelajaran e-learning yang diimplementasikan selama pembelajaran daring sangatlah bermanfaat bagi mahasiswa. Hal ini dibuktikan dengan respons mahasiswa terhadap pertanyaan yang diberikan pada saat pengisian angket dengan menunjukkan hasil cukup positif dengan rata-rata yang menjawab setuju sebesar 63,81%. Berdasarkan data yang didapatkan dari penelitian menunjukkan bahwa e-learning dapat diterapkan dalam pembelajaran online di UIN Walisongo Semarang. Namun penggunaan e-learning tersebut harus selalu ditingkatkan untuk mencapai tujuan pembelajaran yang lebih baik lagi Kata kunci: sistem menejemen pembelajaran daring, calon guru kimia, pandemi covid-19. DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.15